Contracts, Externalities, and Incentives in Shopping Malls - Gould, Eric D.; Pashigian, B. Peter; Prendergast, Canice J. (The Review of Economics and Statistics, 2005)
This paper demonstrates that mall store contracts are written to internalize externalities through both an efficient allocation and pricing of space, and an efficient allocation of incentives across stores. Certain stores generate externalities by drawing customers to other stores, whereas many stores primarily benefit from external mall traffic. Therefore, to varying degrees, the success of each store depends upon the presence and effort of other stores, and the effort of the developer to attract customers to the mall. Using a unique data set of mall tenant contracts, we show that rental contracts are written to (i) efficiently price the net externality of each store and (ii) align the incentives to induce optimal effort by the developer and each mall store according to the externality of each store's effort.